MicroRNA-124 Promotes Singapore Grouper Iridovirus Replication and Negatively Regulates Innate Immune Response - Li, Pin-Hong; Wang, Li-Qun; He, Jia-Yang; Zhu, Xiang-Long; Huang, Wei; Wang, Shao-Wen; Qin, Qi-Wei; Sun, Hong-Yan (Frontiers in Immunology, 2021)
Viral infections seriously affect the health of organisms including humans. Now, more and more researchers believe that microRNAs (miRNAs), one of the members of the non-coding RNA family, play significant roles in cell biological function, disease occurrence, and immunotherapy. However, the roles of miRNAs in virus infection (entry and replication) and cellular immune response remain poorly understood, especially in low vertebrate fish. In this study, based on the established virus-cell infection model, Singapore grouper iridovirus (SGIV)-infected cells were used to explore the roles of miR-124 of Epinephelus coioides, an economically mariculture fish in southern China and Southeast Asia, in viral infection and host immune responses. The expression level of E. coioides miR-124 was significantly upregulated after SGIV infection; miR-124 cannot significantly affect the entry of SGIV, but the upregulated miR-124 could significantly promote the SGIV-induced cytopathic effects (CPEs), the viral titer, and the expressions of viral genes. The target genes of miR-124 were JNK3/p38α mitogen-activated protein kinase (MAPK). Overexpression of miR-124 could dramatically inhibit the activation of NF-κB/activating protein-1 (AP-1), the transcription of proinflammatory factors, caspase-9/3, and the cell apoptosis. And opposite results happen when the expression of miR-124 was inhibited. The results suggest that E. coioides miR-124 could promote viral replication and negatively regulate host immune response by targeting JNK3/p38α MAPK, which furthers our understanding of virus and host immune interactions.